New Thiazolidine-4-One Derivatives as SARS-CoV-2 Main Protease Inhibitors - Antonella Messore; Paolo Malune; Elisa Patacchini; Valentina Noemi Madia; Davide Ialongo; Merve Arpacioglu; Aurora Albano; Giuseppe Ruggieri; Francesco Saccoliti; Luigi Scipione; Enzo Tramontano; Serena Canton; et al. (MDPI AG, 2024)
It has been more than four years since the first report of SARS-CoV-2, and humankind has experienced a pandemic with an unprecedented impact. Moreover, the new variants have made the situation even worse. Among viral enzymes, the SARS-CoV-2 main protease (Mpro) has been deemed a promising drug target vs. COVID-19. Indeed, Mpro is a pivotal enzyme for viral replication, and it is highly conserved within coronaviruses. It showed a high extent of conservation of the protease residues essential to the enzymatic activity, emphasizing its potential as a drug target to develop wide-spectrum antiviral agents effective not only vs. SARS-CoV-2 variants but also against other coronaviruses. Even though the FDA-approved drug nirmatrelvir, a Mpro inhibitor, has boosted the antiviral therapy for the treatment of COVID-19, the drug shows several drawbacks that hinder its clinical application. Herein, we report the synthesis of new thiazolidine-4-one derivatives endowed with inhibitory potencies in the micromolar range against SARS-CoV-2 Mpro. In silico studies shed light on the key structural requirements responsible for binding to highly conserved enzymatic residues, showing that the thiazolidinone core acts as a mimetic of the Gln amino acid of the natural substrate and the central role of the nitro-substituted aromatic portion in establishing π-π stacking interactions with the catalytic His-41 residue.